American vs European public administration: does public administration make the modern state, or does the state make public administration - Stillman, Richard J, II (1997)
"What is Public Administration?" has worried American administrative scholars throughout this century: Is it a discipline? Profession? Field? Focus? Enterprise? Or, what? This essay takes a new look at that old question, one that Dwight Waldo spent much of his academic career wrestling with. It begins by looking at how Dwight Waldo's The Administrative State conceived of the American state, in contrast to the European state experience. The author concludes that Public Administration on both sides of the Atlantic is intricately intertwined with state development, its whole and parts, its past, present and future. Thus, our own Public Administration - and Europe's as well - can only be understood within the peculiar, nation-state context. In Europe literally the state makes Public Administration; whereas within the United States, the reverse can be said to be true. - Reproduced
Keywords: Public administration